Managing proposal sequences in role-play assessment: Validity evidence of interactional competence across levels. (January 2020) - Youn, Soo Jung
This qualitative study reports an investigation of the nature of interactional competence at various levels of achievement in the context of role-play speaking assessment. The focal point of this study is on how examinees jointly accomplish the interactional work involved in proposal sequences in role-play interaction. Based on a conversation analysis of a corpus of role-play interaction, I argue that distinct sequential organizations and interactional features found across examinees' levels serve as critical validity evidence for assessing interactional competence. Various shift markers and stepwise transitions were present in higher-level examinees when they initiated and shifted actions in role-play interaction. However, lower-level examinees' opening turns were typically forwarded without establishing a shared understanding relevant to an upcoming action. When the examinees responded to various proposal sequences, coherent and sufficient topic organizations were recurrent in higher-level performances. The examinees, regardless of levels, managed to close the role-play interaction well. I discuss the implications of the demonstrated link between the recurrent interactional features and examinees' interactional competence for future research into speaking assessment and teaching.